Study the effects of exposure to gases and vapors in the petroleum refinery in Nasiriyah on liver and Renal functions - Abdulhakeem Hassan Albakaa, Ali (Al-Qadisiyah Journal of Pure Science, 2018)
This study is aimed to study the effects of exposure to petroleum gases and vapors on liver and renal functions in workers in Nasiriyah refinery. The research samples included 30 workers and employees working in two locations. There are two petroleum gases and vapors as sections of production and asphalt refinery in Nasiriyah / Iraq and the study also included a control group of 30 samples from the rest of the refinery sites less exposure to petroleum gases and vapors. The most important finding is conducting tests of liver function [(direct bilirubin, indirect bilirubin and total bilirubin), (tests of liver enzymes Included GOT, GPT, ALP)] and renal tests [blood urea and creatinine] for workers in the sections production and asphalt, where our turned out to be working in sections of production and asphalt were no significant differences ​​of blood urea when compared with the same testing rates for the control group. While testing rates values ​​ ​​(creatinine, ALT enzyme, AST enzyme, ALP enzyme, direct bilirubin, indirect bilirubin and total bilirubin) were as statistically significant when compared to the same testing rates for the control group. It turns out that workers are not exposed to health syndromes and disorders.